Nilai-Nilai Pendidikan Islam Serta Hikmah Pengurusan Jenazah - Yunita, Nurma; Valentine, Femalia (Belajea: Jurnal Pendidikan Islam, 2020)
This paper aims to determine the values of Islamic education in the management of remains. This is a library research (library research). Sources of data are books relating to Islamic education and books relating to the maintenance of the bodies. The method (data analysis) used is the method of deduction, induction and comparability. From this study it can be concluded that the values of Islamic education in the management of remains include the education of faith which includes multiplying remembering death, guarding and avoiding oneself from acts of shirk, repentance, being obedient in carrying out Allah’s commands, being patient in worship, being patient when receiving disaster and giving thanks. Which Allah has given and always has the nature of tawadhu. In contrast the values of other Islamic education are social education which includes instilling mutual respect, generosity, being responsible and implementing mutual assistance